2017
DOI: 10.1097/inf.0000000000001625
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Nasopharyngeal Carriage by Haemophilus influenzae in Healthy Children

Abstract: Colonization by NTHi is high in this Mediterranean coast region with remarkable ampicillin resistant. Younger age and the winter period were facilitating factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Colonization with H . influenzae has also been investigated mainly in infants and children [23, 24] for the same reasons. With regard to GAS, prevalence data on asymptomatic colonization have been available for infants or children [25] and also to a smaller extend for elderly people living in long term care facilities [17, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Colonization with H . influenzae has also been investigated mainly in infants and children [23, 24] for the same reasons. With regard to GAS, prevalence data on asymptomatic colonization have been available for infants or children [25] and also to a smaller extend for elderly people living in long term care facilities [17, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Non-encapsulated strains also called "non-typeable" Hi (NTHi), cause usually non-invasive infections of the upper respiratory tract, but can also be responsible for invasive infections (7). Asymptomatic carriage of NTHi strains in healthy children under 5 years of age is common (27.7% with a variation between 73.2% in winter and 26.8% in summer) (8). Carriage of encapsulated strains is rarer especially carriage of Hib in countries where Hib vaccination is included into national immunization schedules (9).…”
Section: Introductionmentioning
confidence: 99%
“…Carriage rates of H. influenzae seem to differ largely in various studies, and the carriage rate in Iceland is considerably higher than was found in most other studies (1620), possibly because of the different climate and/or different time period when samples were collected; however, the lowest carriage rate was found to be similar to that in Holland (15).…”
Section: Discussionmentioning
confidence: 65%